Circadian Gene Expression Regulates Pulsatile Gonadotropin-Releasing Hormone (GnRH) Secretory Patterns in the Hypothalamic GnRH-Secreting GT1-7 Cell Line - Chappell, Patrick E. (Society for Neuroscience, 2003)
Although it has long been established that episodic secretion of gonadotropin-releasing hormone (GnRH) from the hypothalamus is required for normal gonadotropin release, the molecular and cellular mechanisms underlying the synchronous release of GnRH are primarily unknown. We used the GT1-7 mouse hypothalamic cell line as a model for GnRH secretion, because these cells release GnRH in a pulsatile pattern similar to that observed in vivo. To explore possible molecular mechanisms governing secretory timing, we investigated the role of the molecular circadian clock in regulation of GnRH secretion. GT1-7 cells express many known core circadian clock genes, and we demonstrate that oscillations of these components can be induced by stimuli such as serum and the adenylyl cyclase activator forskolin, similar to effects observed in fibroblasts. Strikingly, perturbation of circadian clock function in GT1-7 cells by transient expression of the dominant-negative Clock-Δ19 gene disrupts normal ultradian patterns of GnRH secretion, significantly decreasing mean pulse frequency. Additionally, overexpression of the negative limb clock gene mCry1 in GT1-7 cells substantially increases GnRH pulse amplitude without a commensurate change in pulse frequency, demonstrating that an endogenous biological clock is coupled to the mechanism of neurosecretion in these cells and can regulate multiple secretory parameters. Finally, mice harboring a somatic mutation in the Clock gene are subfertile and exhibit a substantial increase in estrous cycle duration as revealed by examination of vaginal cytology. This effect persists in normal light/dark (LD) cycles, suggesting that a suprachiasmatic nucleus-independent endogenous clock in GnRH neurons is required for eliciting normal pulsatile patterns of GnRH secretion.